2007
DOI: 10.1080/10428190701377055
|View full text |Cite
|
Sign up to set email alerts
|

Gravin gene expression in acute leukaemias: Clinical importance and review of the literature

Abstract: The aim of this study was to determine the expression of Gravin (a tumor suppressor gene belonging to the A kinase anchoring protein family) in samples of acute leukaemia and to explore its association with the prognosis. The study group consisted of 162 people (137 patients with acute leukaemia and 25 volunteers as control). Real-time quantitative PCR was used to determine the gene expression and beta Actin used as a control gene. The results were evaluated with Comparative Ct method. Gravin beta-Actin DeltaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Such observations fit with reports that AKAP12 has been reported to act as a tumour suppressor that blocks the cell cycle and inhibits oncogenic proliferation, invasion, chemotaxis and neovascularization . However, the situation is not at all clear as the expression of the protein is higher in cancer cells which would tend to indicate a positive role in proliferation . Although the role of AKAP12 in endothelial cells has been studied, experiments have concentrated on dermal endothelial cells, as well as immortalized cells and the role of AKAP12 on permeability—little has been done to assess the consequences of AKAP12 on angiogenesis.…”
Section: Introductionsupporting
confidence: 80%
“…Such observations fit with reports that AKAP12 has been reported to act as a tumour suppressor that blocks the cell cycle and inhibits oncogenic proliferation, invasion, chemotaxis and neovascularization . However, the situation is not at all clear as the expression of the protein is higher in cancer cells which would tend to indicate a positive role in proliferation . Although the role of AKAP12 in endothelial cells has been studied, experiments have concentrated on dermal endothelial cells, as well as immortalized cells and the role of AKAP12 on permeability—little has been done to assess the consequences of AKAP12 on angiogenesis.…”
Section: Introductionsupporting
confidence: 80%
“…Due to the fact that Rho GTPases are crucial for the coordination of events required for cell migration [61], this correlates well with the predicted increase of metastatic potential in the absence of NCOR1. AKAP12 has also been described as being induced in colon cancer cells [62]. Another report showed that overexpression of AKAP12 in a CRC cell line inhibited proliferation and anchorage-independent growth, features that correlate well with our observations [63].…”
Section: Discussionsupporting
confidence: 91%
“…Roughly 40% of the Gleason sum 7 to 10 lesions that were deficient AKAP12 staining also exhibited gene deletion, as determined by laser capture microdissection followed by PCR analysis (AKAP12 and GAPDH control primers) (Gelman, unpublished data). Reports showing cancer-related loss of AKAP12 expression include human and rat prostate cancer cell lines, 36 pulmonary adenocarcinomas, 73 leiomymoma, 74 chronic and acute myeloid leukemias and myelodysplastic syndromes, 75-77 multiple myelomas, 78 papillary thyroid carcinoma, 79 pediatric acute lymphoblastic leukemia, 80 gastric cancer, 70 non-small cell lung carcinoma, 81 osteosarcomas, 82,83 melanomas, 84,85 retinoblastomas, 86 colon cancer, 87,88 fibrosarcomas, 89 and squamous cell lung carcinoma. 90,91 In all these cases, AKAP12 transcript levels are suppressed 5- to 15-fold compared to matched controls.…”
Section: Downregulation Of Akap12 In Human Cancersmentioning
confidence: 99%
“…90,91 In all these cases, AKAP12 transcript levels are suppressed 5- to 15-fold compared to matched controls. Many microarray-based studies demonstrate 3- to 10-fold reduction in relative AKAP12 mRNA levels in breast, prostate, lung, and ovarian cancers and in gliomas, 77,92-100 and others have been cited in Entrez GEO (Gene Expression Omnibus; www.ncbi.nlm.nih.gov/geo) or Oncomine (www.oncomine.org) linking AKAP12 expression with tumor suppression. In silico analyses at the Cancer Genome Anatomy Project SAGE (Serial Analysis of Gene Expression) site (http://cgap.nci.nih.gov/SAGE) identify AKAP12 downregulation in human thyroid, lung, and liver cancer tissue and in human ovarian cancer cell lines.…”
Section: Downregulation Of Akap12 In Human Cancersmentioning
confidence: 99%